Muscular workload of veterinary students during simulated open and laparoscopic surgery: A pilot study*. Issue 6 (29th May 2017) - Kilkenny, Jessica; Larson, Dennis J.; MacCormick, Mathew; Brown, Stephen H. M.; Singh, Ameet
Abstract: Objective: To compare upper extremity muscle activity and workload between simulated open surgery, multiple port laparoscopic surgery (MLS), and single incision laparoscopic surgery (SLS) techniques in veterinary students. Study design: Pilot study. Population: Veterinary students (n = 10) from years 1 to 4. Methods: Bipolar skin surface electrodes were fixed bilaterally to the forearm flexor, forearm extensor, biceps brachii, triceps brachii, and upper trapezius muscles. Electromyography data were recorded during one repetition of 2 simulated surgical exercises via open surgery, MLS, and SLS. Participants completed a validated workload survey after each simulated surgical technique. Muscle activity and perceived workload were compared between surgical techniques with 1‐way ANOVAs and Fisher's LSD post hoc tests. Results: Muscle activity during peg transfer was higher with MLS and SLS compared to simulated open surgery in the right and left forearm extensors (both P < .0001), right ( P < .0001) and left biceps ( P = .0005), right triceps ( P = .0004), and right upper trapezius muscles ( P = .0211). Similar results were found for the right and left forearm extensors (both P < .0001), right ( P = .0381) and left ( P = .0147) forearm flexors, right biceps ( P < .0001), and right triceps ( P = .0004) during a simulated suture task. Participants found laparoscopic techniques more mentally demanding, physically demanding, complex, and stressful compared to a simulated open surgical technique. Conclusion: In veterinary students, average muscle activity and perceived workload were highest using MLS and SLS compared to an open surgical technique when performing simulated surgical exercises in a laparoscopic box trainer.